Increased The Cognitive, Effective, and Psychomotor Aspects of Nurses in The Practice of Developmental Care - Mariyam Mariyam; Riwayati Riwayati (Media Keperawatan Indonesia, 2018)
Background: The cause of high infant mortality rate is low birth weight (LBW). Optimal LBW treatment needed that the baby can pass the transition from intrauterine to extrauterine. One of the efforts done is developmental care. Implementation of developmental care requires knowledge, attitudes and skills of nurses. Objective: This study aims to identify the cognitive, affective and psychomotor aspects of nurses in treating LBW before and one month after being given developmental care information at RS Roemani Semarang. Methodology: The design of this research are pre experiment pre and post design. The sample of the study was all nurses in high risk infant room Roemani Hospital Semarang . Sample amounted to 12 respondents. Researchers identify the cognitive, affective and psychomotor aspects of nurses in treating LBW with questionnaires and observations before being given developmental care information. A month after being given information about developmental care researchers re-identify the cognitive, affective and psychomotor aspects of the nurse. Result: Cognitive score of respondent before health education 11.75 and after 13.83 with total score 22, mean affective score of respondent before health education 48,83 and after 52,92 with total score 60, mean of psychomotor score of respondent before health education 2.58 and after 4 with a total score of 4. Based on the results of statistical analysis each show p value 0.00 so that it can be concluded there are differences cognitive, affective and psychomotor nurses in the application of developmental care both before and a month after being given health education. Discussion: In this study post intervention is done month after health education like input from previous researcher Zubaidah, rustina & Sabri (2013) to know the right time in repeating the same information. The results showed that after 30 days showed a cognitive, affective and psychomotor increase, this could be because after given the health education nurses apply in the care of LBW so that knowledge and skills increase.